Validitas Buku Ilmiah Populer Etnobotani Adenostemma lavenia Pada Masyarakat Dayak Bakumpai Desa Bagus Kabupaten Barito Kuala - Halwa, Aulia; Dharmono, Dharmono; Irianti, Riya (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2024)
Validity is an action taken in research to find out the weaknesses and strengths of a product developed in the form of teaching materials. The validated teaching material is a popular scientific book on ethnobotany Adenostemma lavenia in the Bakumpai Dayak community, Bagus Village, Barito Kuala Regency. The validator consists of 2 experts from Lambung Mangkurat University. The research method used is development research with an education Research and Development (RnD) with the Plomp model validity test. The results of the validity of this popular scientific book have a value of 3.6 with very valid criteria.